2022
DOI: 10.1021/acs.jproteome.2c00277
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Top-Down Proteomics Data by Bottom-Up-Based N-Terminomics Reveals Pitfalls in Top-Down-Based Terminomics Workflows

Abstract: Bottom-up proteomics (BUP)-based N-terminomics techniques have become standard to identify protein N-termini. While these methods rely on the identification of N-terminal peptides only, top-down proteomics (TDP) comes with the promise to provide additional information about post-translational modifications and the respective C-termini. To evaluate the potential of TDP for terminomics, two established TDP workflows were employed for the proteome analysis of the nematode Caenorhabditis elegans. The N-termini of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Structure of peptide in protein after broken. The peptide RQQWELQGDRRC is a fragment of Ara h 2 in roasted peanuts. (A, B) Original structure.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structure of peptide in protein after broken. The peptide RQQWELQGDRRC is a fragment of Ara h 2 in roasted peanuts. (A, B) Original structure.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Dimethylation can cause mass increments of 32 Da on the N-termini of proteins, 32 and labeling before digestion partly avoids the disturbance of trypsin peptides. 33,34 As shown in Table 1, we detected five N-termini with dimethyl-labeled (shown in Figures 2A and S1), including the N-termini of mature Ara h 2 (R22, No. 12 in Table 1) and Ara h 3 (I21, No.…”
Section: Detected N-terminalmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, we concluded that avoidance of heating and prolonged exposure to acidic conditions is necessary but also sufficient to prevent artificial cleavage of highly labile peptide bonds. Nevertheless, further studies are needed to clarify the origin of these subsequence proteoforms, that is, if they arise mainly biologically [38][39][40] or artificially, for example, by applying N-terminal labeling strategies [41].…”
Section: Optimization Of Low/low Ph Separationmentioning
confidence: 99%
“… 63 Reductive dimethylation has also been shown to help evaluating N-termini in proteoforms identified by TDP-based terminomics. 63 , 64 …”
Section: Introductionmentioning
confidence: 99%